CONCEPT OF PROFESSIONAL EDUCATION AND ITS CHARACTERISTICS (Proceedings of International Conference on Modern Science and Scientific Studies, 2024)
In the reforms carried out in the field of education, special attention was paid to education and training of the young generation in professions, to prepare them for adult life as professional specialists of any profession.